Enhancing patient satisfaction in COVID-19 wards: a randomized controlled trial on the impact of supportive educational programs in Najaf hospitals - Dhuha Ahmed Al-Qaseer; Mohammad Namazinia; Fatemeh Hajiabadi; Fatemeh Hajiabadi; Seyyed Reza Mazloum; Seyyed Reza Mazloum; Ali A. Al-Fahham (Frontiers in Psychiatry)
BackgroundThe COVID-19 pandemic has severely impacted global health, pervasively affecting the physical and mental wellbeing of individuals worldwide. As the pandemic continues, evaluating patient satisfaction within healthcare has become increasingly critical. This study examines the impact of supportive educational programs on patient satisfaction in COVID-19 wards in Najaf hospitals.MethodA randomized clinical trial involving 60 patients admitted to COVID-19 departments was conducted. The intervention group received a comprehensive supportive educational program upon hospital admission, while the control group received standard care. Participant satisfaction levels were measured using a translated and adapted version of Wolf’s Patient Satisfaction Instrument. Analysis was performed on demographic data and satisfaction scores through descriptive statistics and inferential tests using SPSS version 21.ResultsThe study revealed that the intervention group reported significantly higher satisfaction scores compared to the control group across all measured domains, including professional-technical care, trust, and patient education. These results suggest that supportive educational programs can significantly enhance patient satisfaction during hospitalization for COVID-19.ConclusionSupportive educational interventions are effective in improving patient satisfaction, which is an important metric for healthcare quality. This study indicates that supplementing standard care with educational and emotional support benefits patients, pointing toward the need for integrated care approaches that address both physical and psychological needs during pandemics. Future research could focus on long-term impacts and explore the potential for virtual implementation of similar programs.Clinical trial registrationhttps://irct.behdasht.gov.ir/trial/58407, identifier IRCT20140625018231N1.